Peningkatan Keterampilan Motorik Halus Terhadap Siswa TK Darul Ilmi Murni Melalui Kegiatan Merakit Robot Dengan Barang Bekas Sebagai Permainan Edukatif - Ade Sarah Huzaifah; R. A. Fattah Adriansyah (CV. Aksara Global Akademia, 2024)
Fine motor skills, which involve movements using the small muscles in the hands and wrists, are essential for everyday tasks such as writing, eating, dressing and playing. These skills develop gradually from birth to adulthood and require practice. Hence, it is expected that through the activity of assembling robots with used goods in early childhood can improve children's fine motor skills, improve hand and eye coordination, dexterity, accuracy, strength, creativity, problem solving, and spatial awareness. This activity was carried out with Darul Ilmi Murni Kindergarten students, starting with coordinating with the teacher, preparing activity materials, and presenting the material while practicing it with students. The results of this activity show that assembling robots from used items is not only fun, but also educational. Children are actively involved in processing simple materials into moving robots, while improving their fine motor skills. This activity can also be an effective and fun way to introduce children to the world of technology and support their essential skills development.